Implementasi Sistem Penunjang Keputusan untuk Menentukan Bonus Honor Gaji Guru Bedasarkan Data Jam Lebih Menggunakan Metode Specific Measurable Achievable Relevant Time-Bound (Smart) Berbasis Web (Studi Kasus pada SMK Ikhlas Jawilan) - Mustari Bisri (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Providing teacher bonus pay based on data on excess teaching hours is a form of recognition that can boost teacher morale and performance. However, the process of determining teacher bonus pay at SMK Ikhlas Jawilan is still manual, potentially leading to inefficiency, a lack of objectivity, and the risk of errors in calculations and decision-making. This situation highlights the need for a system that can assist the school in determining teacher bonus pay in a more systematic and measurable manner. This study aims to design and implement a web-based Decision Support System (DSS) for determining teacher bonus pay using the Specific, Measurable, Achievable, Relevant, and Time-Bound (SMART) method. The criteria used in this study include excess teaching hours (inval), the teacher's role as a school organizational leader, and additional duties as laboratory manager, each of which has varying levels of importance. The process of implementing the SMART method in the system begins with determining criteria and weighting. The developed system is web-based, facilitating data management, increasing accessibility, and supporting transparency in the assessment process. The results of the system implementation indicate that the use of a web-based Decision Support System using the SMART method can assist the school in making decisions more objectively, accurately, and efficiently. Furthermore, this system can minimize subjectivity and increase fairness in determining teacher salary bonuses.